Changes in the blood level, efficacy, and safety of tacrolimus in pregnancy and the lactation period in patients with systemic lupus erythematosus. (December 2018) - Hiramatsu, Y; Yoshida, S; Kotani, T; Nakamura, E; Kimura, Y; Fujita, D; Nagayasu, Y; Shabana, K; Makino, S; Takeuchi, T; Arawaka, S
Objectives: We investigated the efficacy and safety of tacrolimus (TAC) by monitoring its serum concentration for mothers and infants in pregnant patients with systemic lupus erythematosus (SLE). Methods: We measured trough concentrations of TAC in 25 pregnant patients with SLE to assess influence of TAC on the disease activity. Additionally, we measured the concentrations of TAC in umbilical arterial blood, breast milk, and breastfed infants to investigate the safety of TAC for the mothers and infants. Results: The trough concentrations of TAC in the mothers significantly decreased in the second trimester as compared with those before pregnancy. However, the decrease in the trough concentrations of TAC did not lead to the deterioration of SLE. When examined, the doses of TAC were significantly lower in the second trimester and postpartum in the deteriorating group than those in the non-deteriorating group. There were no adverse events by TAC in mothers and fetuses. The concentrations of TAC in the umbilical cord blood were lower than those in the maternal blood. The relative infant dose in breastfed infants of TAC was < 1%. The level of TAC in infant bloods was below detectable limits. Conclusion: These findings suggest that TAC is one of the most effective and safest immunosuppressive drugs for use in pregnant patients with SLE.